Quikee eXpress / Nur Adibah Syakirah Alwi... [et.al] - Alwi, Nur Adibah Syakirah; Alphonsus, Dimitri Jimmy; Ayong, Kenneth Bugak; Mitali, Jamilah; Sipat, Nurul Hanie (2010)
Quickee eXpress is a start-up organization that offers a complete car repair service as well as a full-featured retail parts store. will grow into a business with outstanding sales by year three. The auto repair market has a lot of competition; however, almost all only offer service. will differentiate themselves by not only offering a hassle-free repair service, but a fully stocked parts store. Not only will this serve a wide range of customers for both service and parts, but the parts department will support the service department by allowing the service department to turnaround jobs far faster than the competition with generally all of the needed parts in stock and on location.